1998
DOI: 10.1161/01.atv.18.11.1796
|View full text |Cite
|
Sign up to set email alerts
|

NO Inhibits Cytokine-Induced iNOS Expression and NF-κB Activation by Interfering With Phosphorylation and Degradation of IκB-α

Abstract: Abstract-Nitric oxide (NO) is known to have antiatherogenic and anti-inflammatory properties, but its effects on the cytokine-induced nuclear factor-kappa B (NF-B) activation pathway in relation to the regulation of inducible nitric oxide synthase (iNOS) gene in vascular smooth muscle cells (VSMCs) remain elusive. To elucidate the roles of NO in the regulation of cytokine-induced NF-B activation and consequent iNOS gene expression, we studied the effects of synthases (NOSs). Three distinct isozymes of NOS have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(104 citation statements)
references
References 38 publications
6
96
1
1
Order By: Relevance
“…Under basal conditions, ⅐ NO plays a central role in maintaining vascular homeostasis (56)(57)(58)(59). Thus, stimulation of ⅐ NO consumption by monocytes will contribute to proatherogenic conditions by increasing leukocyte adhesion and margination.…”
Section: Discussionmentioning
confidence: 99%
“…Under basal conditions, ⅐ NO plays a central role in maintaining vascular homeostasis (56)(57)(58)(59). Thus, stimulation of ⅐ NO consumption by monocytes will contribute to proatherogenic conditions by increasing leukocyte adhesion and margination.…”
Section: Discussionmentioning
confidence: 99%
“…124 Alternatively, transcriptional induction and stabilisation of the inhibitory molecule IkB, that keeps NF-kB sequestered in the cytoplasm, may account for the inhibition of NF-kB activity. 125 Furthermore, it has been reported that NO inhibits NF-kB activation in rat vascular smooth muscle cells via a cGMP-independent inhibition of the phosphorylation and proteasomal degradation of I-kB, 126 and inhibition of the proteasome by NO has additionally been demonstrated by Glockzin et al 127 in macrophages. The result of such inhibition would be downregulation of survival factors under the control of this transcription factor, such as the antiapoptotic Bcl-2 family members.…”
Section: Proapoptotic Mechanismsmentioning
confidence: 93%
“…Examples include aspirin, 230,231 (sodium salicylate), ibuprofen, 232 nitric oxide, [233][234][235] prostoglandin A1, 236 sanguinarine, 237 and YopJ (encoded by Yersinia pseudotuberculosis). 238 Recently, 4-hydroxy-2-nonenal, a lipid peroxidation product, has been shown to block phosphorylation by direct inhibition of IKK.…”
Section: Block Phosphorylation Of I Bmentioning
confidence: 99%